ATRT-22. Outcomes for children with recurrent atypical teratoid rhabdoid tumor: A single institution study with updated molecular and germline analysis. (3rd June 2022) - Carey, Steven S; Huang, Jie; Myers, Jason R; Mostafavi, Roya; Orr, Brent; Michalik, Layna H; Klimo, Paul; Boop, Frederick; Nichols, Kim E; Merchant, Thomas; Ellison, David W; Robinson, Giles W; et al.
Abstract: BACKGROUND: Children with recurrent atypical teratoid rhabdoid tumor (recATRT) who fail frontline therapies have dismal outcomes. The association of ATRT molecular groups (SHH, TYR and MYC) and presence of underlying cancer predisposition with survival post-recurrence (postRD) is unknown. METHODS: We previously reported outcomes from a single-institution retrospective study of children <21 years with recATRT treated at St. Jude Children's Research Hospital from 2000 to 2020. Herein we report updated progression-free survival (PFS2: time from initial recurrence to subsequent first progression) and overall survival (OSpostRD: time from initial recurrence to death/last follow-up) outcomes by molecular groups determined by tumor DNA methylation and by germline SMARCB1/SMARCA4 alterations (GLA). RESULTS: Median age and time from initial diagnosis to recurrence for 64 eligible patients were 2.1 years (range: 0.5-17.9 years) and 5.4 months (range: 0.5–125.6 months), respectively. The 2- and 5-year PFS2 and OSpostRD were 3.1% (±1.8%)/1.6% (±1.1%) and 20.3% (±4.8%)/7.9% (±3.8%), respectively. PFS2 did not differ by molecular groups (p=0.210) for 42 participants with available data (MYC=11, SHH=21, TYR=10). Children with TYR group had a better 2-year OSpostRD [60.0% ±14.3% (TYR) vs. 18.2% ±9.5% (MYC) or 4.8% ±3.3% (SHH)] (p=0.018). In univariate analyses, OSpostRD was also better with older age at diagnosis (≥ 1 year vs <1 year; p=0.03), female gender (p=0.008), and metastatic site of recurrence compared to local or combined sites of disease (p<0.001). OSpostRD did not differ for those with positive GLA (n=12) compared to those without (n=21) (p=0.231). Only 6 children (9.4%) (TYR=4, SHH=1, NA=1) were alive at median follow-up of 7.7 years from recurrence. CONCLUSION: Children with recATRT have extremely poor outcomes. Older age at diagnosis, female gender, TYR group, and metastatic site of initial recurrence were associated with longer survival in our study. These results reinforce the dire need for better therapeutic options.